Multiple Positive Solutions for Singular Semipositone Periodic Boundary Value Problems with Derivative Dependence - Huiqin Lu (Journal of Applied Mathematics)
By constructing a special cone in C1[0,2π] and the fixed point theorem, this paper investigates second-order singular semipositone periodic boundary value problems with dependence on the first-order derivative and obtains the existence of multiple positive solutions. Further, an example is given to demonstrate the applications of our main results.